2015
DOI: 10.1016/j.jallcom.2015.01.234
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural design of new high conductivity – high strength Cu-based alloy

Abstract: a b s t r a c tSome novel high conductivity-high strength materials were designed in the binary Cu-Mg. They exhibit an excellent balance between strength and electrical properties. The properties and the performance of the designed materials are compared with the main Cu-based alloys and the analysis shows that they perform equally to the best one (Cu-Be). Furthermore, we show that an increase of Mg content modifies the microstructure feature and leads to a strong increase of strength without any significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…The rapid development of IC technology towards high density, multifunction, miniaturization and low cost, desires the copper alloys having higher performances on the mechanical strength, the electrical conductivity, etc. 1,2 For example, the traditional copper alloys, including Cu-Fe-P, Cu-Ni-Si and Cu-Cr-Zr alloys, are hardly be used in the next generation of very-large-scale integration (VLSI) ICs, which requires a ultimate tensile strength (UTS) over 800 MPa and an electrical conductivity (EC) over 50.0% International Annealed Copper Standard (IACS). [3][4][5] To improve the mechanical and electrical properties of copper alloys, one or more alloying elements, such as Ti, Co, P, Mg, Cr, Zr, Be, and Fe, can be introduced.…”
Section: Intorductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid development of IC technology towards high density, multifunction, miniaturization and low cost, desires the copper alloys having higher performances on the mechanical strength, the electrical conductivity, etc. 1,2 For example, the traditional copper alloys, including Cu-Fe-P, Cu-Ni-Si and Cu-Cr-Zr alloys, are hardly be used in the next generation of very-large-scale integration (VLSI) ICs, which requires a ultimate tensile strength (UTS) over 800 MPa and an electrical conductivity (EC) over 50.0% International Annealed Copper Standard (IACS). [3][4][5] To improve the mechanical and electrical properties of copper alloys, one or more alloying elements, such as Ti, Co, P, Mg, Cr, Zr, Be, and Fe, can be introduced.…”
Section: Intorductionmentioning
confidence: 99%
“…2,26 The main role of trace Zn and Sn elements is to increase the energy of the stacking faults of the matrix, which improves the UTS, but has a negative influence on the EC. 1 The main role of trace Mg and P elements is to purify the melt and increase the fluidity of the melt during melting and casting. 32,35 It is also shown that the addition of P can promote the precipitation of the strengthening phases and Cr particles, 34,35 and thus can enhance the strengthening effect of Ni, Si, and Cr.…”
Section: Construction and Application Of A Property-oriented Mldsmentioning
confidence: 99%
“…Gorsse et al [83] prepared Cu-Mg alloys with different Mg contents (4.1 at.%, 8.1 at.%, 23.1 at.%). It was found that with the increase of Mg content, the strength of the alloy increased and the conductivity decreased, it was attributed to the high density of Cu 2 Mg nanoparticles precipitate ( Figure 14).…”
Section: Cu-7agmentioning
confidence: 99%
“…Color online) Calculated strengthening contributions for the casted Cu-Mg alloys. Cu-4.1Mg is a single-phase fcc-Cu(Mg) solid solution; Cu-8.1Mg is composed of fcc-Cu(Mg) and eutectic aggregates, and Cu-23.1Mg consists of fully eutectic structure[83].…”
mentioning
confidence: 99%
“…In the last decades, growing attention has been focused on the development of copper-based alloys with high strength and good electrical conductivity [1]. In recent times, there have been appearing more and more works investigating the structures and properties of conductive materials based on the Cu-Mg alloys strengthened by different SPD-methods [1 -3].…”
Section: Introductionmentioning
confidence: 99%